Smart Medical Information Technology for Healthcare (SMITH) - Winter, Alfred; Stäubert, Sebastian; Ammon, Danny; Aiche, Stephan; Beyan, Oya; Bischoff, Verena; Daumke, Philipp; Decker, Stefan; Funkat, Gert; Gewehr, Jan E.; de Greiff, Armin; Haferkamp, Silke; Hahn, Udo; Henkel, Andreas; Kirsten, Toralf; Klöss, Thomas; Lippert, Jörg; Löbe, Matthias; Lowitsch, Volker; Maassen, Oliver; Maschmann, Jens; Meister, Sven; Mikolajczyk, Rafael; Nüchter, Matthias; Pletz, Mathias W.; Rahm, Erhard; Riedel, Morris; Saleh, Kutaiba; Schuppert, Andreas; Smers, Stefan; Stollenwerk, André; Uhlig, Stefan; Wendt, Thomas; Zenker, Sven; Fleig, Wolfgang; Marx, Gernot; Scherag, André; Löffler, Markus (Methods of Information in Medicine, 2018)
Introduction: This article is part of the Focus Theme of Methods of Information in Medicine on the German Medical Informatics Initiative. “Smart Medical Information Technology for Healthcare (SMITH)” is one of four consortia funded by the German Medical Informatics Initiative (MI-I) to create an alliance of universities, university hospitals, research institutions and IT companies. SMITH’s goals are to establish Data Integration Centers (DICs) at each SMITH partner hospital and to implement use cases which demonstrate the usefulness of the approach.Objectives: To give insight into architectural design issues underlying SMITH data integration and to introduce the use cases to be implemented.Governance and Policies: SMITH implements a federated approach as well for its governance structure as for its information system architecture. SMITH has designed a generic concept for its data integration centers. They share identical services and functionalities to take best advantage of the interoperability architectures and of the data use and access process planned. The DICs provide access to the local hospitals’ Electronic Medical Records (EMR). This is based on data trustee and privacy management services. DIC staff will curate and amend EMR data in the Health Data Storage.Methodology and Architectural Framework: To share medical and research data, SMITH’s information system is based on communication and storage standards. We use the Reference Model of the Open Archival Information System and will consistently implement profiles of Integrating the Health Care Enterprise (IHE) and Health Level Seven (HL7) standards. Standard terminologies will be applied. The SMITH Market Place will be used for devising agreements on data access and distribution. 3LGM2 for enterprise architecture modeling supports a consistent development process.The DIC reference architecture determines the services, applications and the standards-based communication links needed for efficiently supporting the ingesting, data nourishing, trustee, privacy management and data transfer tasks of the SMITH DICs. The reference architecture is adopted at the local sites. Data sharing services and the market place enable interoperability.Use Cases: The methodological use case “Phenotype Pipeline” (PheP) constructs algorithms for annotations and analyses of patient-related phenotypes according to classification rules or statistical models based on structured data. Unstructured textual data will be subject to natural language processing to permit integration into the phenotyping algorithms. The clinical use case “Algorithmic Surveillance of ICU Patients” (ASIC) focusses on patients in Intensive Care Units (ICU) with the acute respiratory distress syndrome (ARDS). A model-based decision-support system will give advice for mechanical ventilation. The clinical use case HELP develops a “hospital-wide electronic medical record-based computerized decision support system to improve outcomes of patients with blood-stream infections” (HELP). ASIC and HELP use the PheP. The clinical benefit of the use cases ASIC and HELP will be demonstrated in a change of care clinical trial based on a step wedge design.Discussion: SMITH’s strength is the modular, reusable IT architecture based on interoperability standards, the integration of the hospitals’ information management departments and the public-private partnership. The project aims at sustainability beyond the first 4-year funding period.
Keywords: Health information interoperability; inte grated advanced information management systems; systems integration; phenotyping; intensive care; antimicrobial stewardship